Дослідження фітосанітарного стану інтродукованих видів роду Iris L. в Донецькому ботанічному саду НАН України - Bondarenko-Borisova, I.V.; Popov, G.V.; Peltikhina, R.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The data on basic pests and diseases of irises in collection of Donetsk Botanical Gardens of the NAS of Ukraine are given. The basic struck culture was Iris hybrida hort., the basic pest was iris root-maggot fly, the basic disease was heterosporiosis. The methods of protection of irises from pest organisms are offered. The steady species and cultivars of irises is distinguished.